Sustainability Business Strategy in the Era of VUCA - Ashari, Denny Rakhmad Widi; Waskita, Gautama Sastra (SINDA: Comprehensive Journal of Islamic Social Studies, 2025)
Sustainability Business Strategy in the Era of VUCA: Dynamic Capability Perspective. The increasing uncertainty and complexity in the business environment, often described as the VUCA (volatility, uncertainty, complexity, and ambiguity) era, pose significant challenges for small and medium-sized enterprises (SMEs) in sustaining their competitive advantage. While sustainability-driven business strategies have been widely acknowledged as a means to enhance long-term resilience, the role of dynamic capabilities in enabling SMEs to navigate sustainability challenges remains underexplored. This study aims to investigate how SMEs develop sustainable business strategies through dynamic capability mechanisms (sensing, seizing, and transforming), using Kedai Kosim, Indonesia, as a case study. Employing a qualitative approach with in-depth interviews and document analysis, this research reveals that strategic agility, stakeholder collaboration, and digital transformation are key enablers of sustainability in resource-constrained firms. The findings extend the dynamic capability theory by contextualizing it within SME sustainability strategies and offer practical insights for business practitioners and policymakers. The study suggests that SMEs can achieve sustainability by embedding it into core business models, leveraging technology, and fostering ecosystem partnerships. This research contributes to the ongoing discourse on sustainability and strategic agility in SMEs, highlighting the need for further empirical exploration across different industries and cultural contexts.